Cognitive symptomes associated with antipsychotic course experience in residual schizophrenia - Safonov, D. M.; Сафонов, Дмитро Миколайович (My University, 2021)
Urgency. The cognitive symptoms of schizophrenia are recognized either as a part of a negative complex of symptomatic, where cognitive malfunction seem to be the secondary complication of emotional and motivational dysregulation; or as a separate group of schizophrenia manifestations that constitutes a massive part of a residual condition. Aim – to evaluate the cognitive functioning and analyze its violation levels in association with antipsychotic course experience in patients with residual schizophrenia. Materials and methods. A study was performed on 100 patients of Zaporozhye Regional Clinical Psychiatric Hospital who were treated as inpatients with diagnosis of recurrent schizophrenia (ICD-10:F20.5). The methods used: anamnestic psychodiagnostics and statistical. As a main psychodiagnostics tool we used “Brief Assessment of Cognition in Schizophrenia”. Results. The assessment of cognitive functions was established by direct testing in clinical setting. Education in years varied from 9 to 16, mean 11,27±2,12 in the population under study. The basic level of cognitive impairment was established: verbal memory test result was 31,6±11,6; digit sequencing test result was 13,4±5,7; token motor task test result was 40,1±18,3; verbal fluency test result was 41,2±10,7; symbol coding test result was 30,6±13,1; tower of london test result was 12,2±4,5. Some correlations were found: for chlorpromazine we can assume minor negative impact on token motor task (r= -0,22) and verbal fluency test (r= -0,27) results; for haloperidol we can assume more pronounced but still minor impact on token motor task (r= -0,22), verbal fluency test (r= -0,27), verbal memory test (r= -0,28) and tower of London test (r= -0,20) results; for trifluoperazine we can see minor negative impact on verbal fluency test (r= -0,26); for clozapine we can’t find any representative correlations with cognitive tests; chlorprothixene as we can assume have minor negative impact on verbal memory test (r= -0,32) result, but minor positive – on tower of London test (r= 0,21) result; for risperidone also assume minor positive impact on sequence coding test (r= 0,25), but other tests in battery show no significant correlations; for zuclopenthixol we can assume minor negative impact on token motor task (r= -0,22) and verbal fluency test (r= -0,31) results.
Keywords: cognitive function; organic brain impairment; residual schizophrenia